2006
DOI: 10.1016/j.bbr.2006.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus accumbens lesions decrease sensitivity to rapid changes in the delay to reinforcement

Abstract: Both humans and non-humans discount the value of rewards that are delayed or uncertain, and individuals that discount delayed rewards at a relatively high rate are considered impulsive. To investigate the neural mechanisms that mediate delay discounting, the present study examined the effects of excitotoxic lesions of the nucleus accumbens (NAC) on discounting of reward value by delay and probability. Rats were trained on delay (n = 24) or probability discounting (n = 24) tasks. Following training, excitotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 45 publications
(66 reference statements)
5
73
1
3
Order By: Relevance
“…A recent study by Acheson et al (2006) reported findings that are in apparent contrast with the findings of Cardinal et al (2001Cardinal et al ( , 2003. Acheson et al (2006) used an adjusting amount schedule (Richards et al 1999) in which the delay to a liquid reinforcer of fixed volume was held constant while the volume of an immediate reinforcer was varied in response to the animals' choices.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…A recent study by Acheson et al (2006) reported findings that are in apparent contrast with the findings of Cardinal et al (2001Cardinal et al ( , 2003. Acheson et al (2006) used an adjusting amount schedule (Richards et al 1999) in which the delay to a liquid reinforcer of fixed volume was held constant while the volume of an immediate reinforcer was varied in response to the animals' choices.…”
Section: Discussionmentioning
confidence: 65%
“…Acheson et al (2006) found that while the lesion had no effect on performance when the delay was held constant, lesioned rats showed flatter preference functions when the delay was changed from day to day. Acheson et al (2006) proposed that the lesion may have disrupted the ability of the rats to adapt to changes in delay, without altering the rate of delay discounting. The present finding of flatter slopes of the psychometric function and larger Weber fractions is consistent with the suggestion that discrimination of within-session changes in d B was less precise in the AcbC-lesioned rats than in the intact rats.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations